Analysis of Mandailing Natal District Court Decision Number 96/Pid.Sus/2022/Pn Mandailing Natal Against Illegal Gold Mining Perpetrators - Sari, Wilda (Universitas Ibn Khaldun Bogor, 2025)
The purpose of this research is to find out, understand and analyze the basis of the judge's considerations in determining guilt and determining the severity of the crime against the defendant for illegal gold mining in Mandailing Natal (Decision Analysis Number 96/PID.SUS/2022/PN MDL). The research method used is normative legal research with statutory, conceptual and case approaches. Types and sources of legal materials, namely primary, secondary and tertiary legal materials obtained by conducting document studies. Analysis of legal materials is carried out by interpretation. The conclusion from this research is that the judge's basis for determining the defendant's guilt is to prove the elements of the article contained in the alternative indictment. The consideration of the panel of judges in determining the severity of the crime against the defendant takes into account both juridical considerations and non-juridical considerations such as sociological considerations and considerations.